BENTUK PENYAJIAN TARI PIRIANG HOYAK BADARAI DI SANGGAR MINANG MAIMBAU KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Shindy Mutiara Dewi; Mansyur, Herlinda (Universitas Negeri Padang, 2025)
This research aims to describe and reveal the form of presentation of the Piriang Hoyak Badarai Dance at the Minang Maimbau Studio, Lubuk Sikaping District, Pasaman Regency. This type of research is qualitative research with descriptive methods. The object of the research is the Piriang Hoyak Badarai Dance at the Minang Maimbau Studio, Lubuk Sikaping District, Pasaman Regency. The research location is Nagari Durian Tinggi, Lubuk Sikaping District, Pasaman Regency. The research instrument is the researcher himself. Data collection techniques using literature study, observation and interviews. Data analysis techniques by collecting data, reducing data, presenting data and drawing data conclusions. The general research results show that the Piriang Hoyak Badarai Dance at the wedding party on June 2 2025, 14.30 in Nagari Durian Tinggi, Lubuk Sikaping District, Pasaman Regency is one of the creative dances. The Piriang Hoyak Badarai dance is a dance that does not tell a story or is non-representational, that is, a dance that does not depict anything. The elements of the presentation form of the Piriang Hoyak Badarai Dance are: (1) Consisting of the gelek movement, rotating stab movement, latak movement, rotating sauak movement, hidang movement, puta lapan movement, circular movement, piriang stomping movement, basilang movement, glass attraction, fire attraction and swinging movement, (2) There are 5 dancers, 4 female dancers and 1 male dancer, (3) The floor design uses a zig-zag floor design and floor design. circles and horizontal line patterns. (4) This dance music uses 4 musical instruments, namely talempong set 1, jimbe, tansa and tambua, (5) The make-up worn by female dancers is beautiful make-up with clothes using kuruang, black sarawa kabasaran and songket behind as well as other accessories and the clothes worn by male dancers are black sarawa kabasaran and songket sasampiang with heads wearing deta, (6) Props use plates, glass and fire, (7) The performance venue is the yard of the house, the exact location of the party. in front of the aisle with a duration of 12 minutes.